ANALISIS PERHITUNGAN, PEMOTONGAN DAN PENYETORAN PAJAK PENGHASILAN PASAL 21 ATAS TAMBAHAN PENGHASILAN PEGAWAI NEGERI SIPIL PADA DINAS KESEHATAN KABUPATEN KUTAI TIMUR - Andi Indrawati 3, Safaruddin, Mardiana 2 (EKONOMIA, 2021)
This research aims to analiyse the calculation, cuts and deposits of income tax article 21 for the additional incame og civil servants conduted by the Treasurer of the Health Office of East Kutai District accordance with regulation of the Minister of Finance No. 262/PMK. 03/2010.The research methods to be used consist of several elements, including types of data collection, details of the required data and data collection techniques to analyse and test the hypothesis expressed above it is necessary to analyze the tax withholding rate and its application based on regulation of the Minister of Finance No. 262/PMK. 03/2010.The results of this research are based on regulation of the Minister of Finance No. 262/PMK. 03/2010 from the data that has been analyzed that additional income is included in any other remuneration under any name that becomes the expenseÂ  of the APBD subject to income tac of article 21 shall be final.